Enhancing Entrepreneurial Competence of Students at Kulliyatul Muallimin al-Islamiyah for Engagement in the Halal Industry Sector - Hadiyanto Arief (Proceeding of International Conference on Islamic Boarding School, 2025)
This study explores the integration of entrepreneurship education within the Kulliyatul Mu’allimin al-Islamiyah (KMI) curriculum, with a particular focus on preparing students (santri) to actively participate in the growing halal industry. In light of the rapid expansion of the global halal market, Islamic educational institutions such as pesantren hold a strategic position in developing entrepreneurs who are both competent and committed to Islamic ethical values. Employing a qualitative descriptive approach, data were collected through literature review, curriculum analysis, and in-depth interviews with teachers and alumni from pesantren implementing the KMI curriculum. The findings indicate that entrepreneurial education at KMI implicitly embeds core Islamic business values such as honesty, responsibility, and a commitment to community welfare, aligning well with the principles of the halal industry. However, the study also identifies significant challenges, including limited access to halal certification training, lack of market exposure, and insufficient collaboration with industry stakeholders. The study concludes that the KMI curriculum holds great potential to be developed as a value-based entrepreneurship education model, capable of producing professional, ethical, and globally adaptive halal entrepreneurs.